Scientific Study of Balance (al-Mīzān) in the Light of Sūrah Al-Rahmān - Researcher (مجلة العلوم الإسلامية والدينية, 2016)
This article is an attempt to elaborate the phenomenon of equilibrium prevailing everywhere in the microcosmic and macrocosmic systems associated with universal stability and rhythm. It has been accentuated what is beautifully illuminated in the beginning verses of Sūrah Al-Rahmān successively regarding balance that invites one’s thought towards the well controlled cosmic system as well as with the concept of balance by means of different manners as identified by exegetes and scholars concerning daily life i.e. from simple and common to that of complex issues and intricacies. Qualitative method has been employed for this research while some aspects have also been handled in accordance with quantitative approach. Article also emphasized the series of cause and effect nexus may be declared as self explanatory episode an indication towards a Supreme Force whose widespread control and interference can’t be denied rationally. Sūrah beautifully pictured the physical and metaphysical sketch of balance having many dimensions from man to universe and vice versa as well as from both towards Ultimate Reality whose dominion is limitless where one has to follow peaceful living and to put oneself aside indulging any disruption from ordinary clash to that of nuclear war to be waged.